2017
DOI: 10.1038/sc.2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress following spinal cord injury: a systematic review of risk and vulnerability factors

Abstract: Combinations of peri- and post-injury factors appear to be influential in the development of PTSD among persons with SCI. Further studies are needed to extrapolate these findings to the broader spinal cord-injured population. More longitudinal research, driven by multicausal models of causation such as the diathesis-stress model, is also needed to determine the temporality of PTSD risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 83 publications
2
17
0
4
Order By: Relevance
“…The relationships between the demographic and injuryrelated variables and the five psychological outcomes were examined. Consistent with the existing studies [8,32,36], factors including age, age at injury, gender, and marital status were all shown to be related to psychological morbidities. The findings showed that older people, males, single or divorced individuals, and patients in the early stage of injury were most susceptible to the psychological disorders.…”
Section: Variablessupporting
confidence: 84%
“…The relationships between the demographic and injuryrelated variables and the five psychological outcomes were examined. Consistent with the existing studies [8,32,36], factors including age, age at injury, gender, and marital status were all shown to be related to psychological morbidities. The findings showed that older people, males, single or divorced individuals, and patients in the early stage of injury were most susceptible to the psychological disorders.…”
Section: Variablessupporting
confidence: 84%
“…Spinal injury patients often have psychological problems such as low total self-concept, acute stress disorder/PostTraumatic Stress Disorder (PTSD) symptoms, and/or suicidal thoughts and behavior (Jurisić and Marusic, 2009 ; Kennedy and Garmon-Jones, 2017 ). According to a review by Pollock et al ( 2017 ), patients having negative thoughts and emotions related to their injury have lower levels of acceptance of their injury, poorer adjustment to being disabled, and report more severe PTSD symptoms (Pollock et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is a traumatic event that impairs sensory, autonomic, and/or motor function. As such, SCI may also lead to long-term psychological sequels such as post-traumatic stress disorder (PTSD) [1][2][3][4][5][6][7], anxiety, and distress [2,4,8]. Studies suggest that traumatic events may lead to the co-existence of PTSD and chronic pain [9][10][11] yet only a few studies documented this co-existence among individuals with SCI.…”
Section: Introductionmentioning
confidence: 99%